1994
DOI: 10.1177/089198879400701s04
|View full text |Cite
|
Sign up to set email alerts
|

Placebo-Controlled Double-Blind Study Examining the Effectiveness of an Hypericum Preparation in 105 Mildly Depressed Patients

Abstract: One hundred and five outpatients with mild depressions of short duration were treated in a double-blind study with either 3 x 300 mg hypericum extract or placebo. The therapy phase was 4 weeks. The effectiveness was judged according to the Hamilton Depression Scale after 2 and 4 weeks. The values of the mean basic score in these periods fell from 15.8 to 9.6 or 7.2 in the active group, and in the placebo group, from 15.8 to 12.3 and 11.3. The difference between active and placebo groups were statistically sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
1

Year Published

1999
1999
2013
2013

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 1 publication
0
25
0
1
Order By: Relevance
“…Several placebo-controlled studies have shown a superior efficacy of hypericum extracts compared to placebo in mild-to-moderate depression. [59][60][61][62] The overall significant superiority of St John's Wort over placebo was also confirmed by a recent meta-analysis. 3 The responder rates for persons receiving hypericum preparations and placebo were 56% and 25% respectively.…”
Section: Clinical Pharmacology and Efficacy In Mild Depressionmentioning
confidence: 53%
“…Several placebo-controlled studies have shown a superior efficacy of hypericum extracts compared to placebo in mild-to-moderate depression. [59][60][61][62] The overall significant superiority of St John's Wort over placebo was also confirmed by a recent meta-analysis. 3 The responder rates for persons receiving hypericum preparations and placebo were 56% and 25% respectively.…”
Section: Clinical Pharmacology and Efficacy In Mild Depressionmentioning
confidence: 53%
“…The 2 most common methodological weaknesses found among these 8 trials were failure to perform an intention-to-treat analysis [10][11][12]14,15 and failure to test the statistical significance of the differences in responder rates between active and placebo groups.…”
Section: Methodsological Qualitymentioning
confidence: 99%
“…The 8 studies that met our inclusion criteria for trials of efficacy [10][11][12][13][14][15][16][17] were generally of high methodological quality: all 8 studies presented comparison demographic data and baseline depression scores for both treatment and control groups; all but one of the studies described steps taken to ensure reliable blinding 10 ; all 8 studies gave a full accounting of subject dropouts; and all but one of the studies 14 reported data using a standard definition of "responder," which is commonly used in the assessment of antidepressants. 28 This definition of "responder" is based on the Hamilton Rating Scale for Depression (HAMD) an extensively validated 9 observer-rated scale calculated from a 21-item questionnaire, which focuses primarily on the somatic symptoms of depression.…”
Section: Methodsological Qualitymentioning
confidence: 99%
See 1 more Smart Citation
“…Its administration in somatoform disorders is primarily based on diagnostic overlaps between depressive or anxiety and somatoform disorders (Linde 2009). Several studies on the efficacy of St John's Wort for mild depression could demonstrate an additional positive effect on somatoform symptoms such as headache or gastrointestinal complaints (e.g., Sommer 1993;Woelk 2000). The effect of Hypericum extracts, and especially hyperforin and adhyperforin, could be mediated by their function as potent but non-specific inhibitors of the synaptosomal reuptake of serotonin, norepinephrine, and dopamine (Butterweck 2003).…”
Section: Natural Productsmentioning
confidence: 99%